ANALISIS PENGARUH KEBIJAKAN PENGUMUMAN DEVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE DI BURSA EFEK JAKARTA PERIODE 2002-2004 - Susanto, Barkah (Universitas Muhammadiyah Magelang, 2006)
Every company in its capital allocation is always given on two interconnected and important problem, that is decisionof long-range expenditure and invesment. Despitefully still there are one problem again that is containing dividend decision about how many dividend which must be alloted o stockholder. Policy of dividend Announcement present one of important decision in its bearing with the effort to maximize the company value influenced by invesment decision, capital structure (decision of accomplishment of fund requirement) and policy of itself dividend. Persuant to the kondidi hence this research take the title :